Fecal Microbiomes Distinguish Patients With Autoimmune Hepatitis From Healthy Individuals - Lou, Jiamin; Jiang, Yan; Rao, Benchen; Li, Ang; Ding, Suying; Yan, Hang; Zhou, Heqi; Liu, Zhenguo; Shi, Qingmiao; Cui, Guangying; Yu, Zujiang; Ren, Zhigang (Frontiers in Cellular and Infection Microbiology, 2020)
Objective: The intestinal microbiome is associated with various autoimmune diseases. Regional difference is the main influencing factor of intestinal microbial difference. This study aimed to identify the differences in fecal microbiome between autoimmune hepatitis (AIH) patients and healthy controls (HCs) in Central China, and to validate the efficacy of fecal microbiome as a diagnostic tool for AIH. Design: We collected 115 fecal samples from AIH patients (N = 37) and HCs (N = 78) in Central China and performed gene sequencing. Fecal microbiomes were characterized and microbial markers for AIH were identified. Results: Fecal microbial diversity showed a downward trend in AIH compared with HCs. Fecal microbial communities significantly differed between both groups. At the phylum level, Verrucomicrobia abundance was significantly increased, while Lentisphaerae and Synergistetes were significantly decreased in the AIH patients versus the HCs. Compared to the HCs, fifteen genera, including Veillonella, Faecalibacterium and Akkermansia, were enriched, while nineteen genera, such as Pseudobutyrivibrio, Lachnospira and Ruminococcaceae, were decreased in the AIH patients. Ten genera, including Veillonella, Faecalibacterium and Akkermansia, predominated in the AIH patients. Five microbial biomarkers were deemed optimal diagnostic tools for AIH. The probability of disease was significantly increased in AIH group versus HCs, achieving 83.25% value of area under the curve. Conclusion: We present the characteristics of AIH patients in Central China for the first time. Five microbial biomarkers, including Lachnospiraceae, Veillonella, Bacteroides, Roseburia and Ruminococcaceae, achieved a high potential distinguishing AIH patients from HCs.